An Application of Interval Rough Pythagorean Fuzzy Set in a Multi Attribute Decision Making Problem - lakshmi, P. Dhanalakshmi (International Journal of Mathematics And its Applications, 2023)
This paper aims to define the cosine, sine and cotangent similarity measures of interval rough pythagorean sets and investigate some properties. Furthermore, based on these proposed measures, a multi attribute decision making problem is solved. Finally, through an example to demonstrate the applicability of the proposed measures.